PERAN INVESTASI DAN DIVIDEN TERHADAP PROFIT PERBANKAN DAN IMPLIKASINYA PADA NILAI PERUSAHAAN - Azizi, Enji (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
This study aims to examine the effect of investment decisions and dividend policy on firm value through profitability as an intervening variable. The investment decision in this research is proxied through Price Earning Ratio (PER); Dividend policy through Divident Payout Ratio (DPR), Profitability through Return on Equity (ROE) and Firm Value through Price to Book Value (PBV). The research population is banking companies listed on the Indonesian Stock Foam (IDX) for the period 2019-2023. Data analysis used intervening regression processed with the SPSS program. The results showed that investment decisions have a positive and significant effect on firm value. Dividend policy not significant effect on firm value. Investment decisions have a negative and significant effect on company profitability. Dividend policy not significant effect on company profitability. Profitability has a positive and significant effect on company profitability. There is no mediation of investment decisions on firm value through profitability as an intervening variable. There is no mediation of dividend policy on firm value through profitability as an intervening variable